2019
DOI: 10.2495/sdp-v14-n2-105-117
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of precipitation and evapotranspiration estimates from Worldclim and Chelsa datasets: Improving long-term water balance at the watershed-scale in the Urabá region of Colombia

Abstract: In this paper, we have evaluated high-resolution spatial gridded climate data from two long-term global datasets, WorldClim V.2.0 and Chelsa V.1.2, in representing variables like precipitation and temperature for the urabá region of Colombia. additionally, climate variables from these datasets have been used to estimate evapotranspiration using traditional methods such as the Turc, hargreaves and Thornthwaite equations. finally, the results of long-term spatial climate characterization are used to apply the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…CHIRPS provided the best estimate of rainfall magnitude both inside and outside forest, increasing linearly with observed values and explaining around half the variation for in situ rain gauges. Other studies have found CHIRPS to be the best option in tropical regions (Beck et al ., 2017), although WorldClim and Chelsa explained >70% of the variation for higher density stations in Brazil and Colombia (Bastidas Osejo et al ., 2019; de Oliveira‐Júnior et al ., 2021). In northern Peru, CHIRPS predicted rainfall greater than 150 mm·month −1 and 1,000 mm·year −1 poorly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHIRPS provided the best estimate of rainfall magnitude both inside and outside forest, increasing linearly with observed values and explaining around half the variation for in situ rain gauges. Other studies have found CHIRPS to be the best option in tropical regions (Beck et al ., 2017), although WorldClim and Chelsa explained >70% of the variation for higher density stations in Brazil and Colombia (Bastidas Osejo et al ., 2019; de Oliveira‐Júnior et al ., 2021). In northern Peru, CHIRPS predicted rainfall greater than 150 mm·month −1 and 1,000 mm·year −1 poorly.…”
Section: Discussionmentioning
confidence: 99%
“…Using different interpolation versus statistical downscaling approaches, on average WorldClim was within 1°C outside forest whereas Chelsa was within 1°C inside forest, an improvement for forest biodiversity studies. WorldClim also overestimated maximum temperatures in tropical rainforest (Jucker et al ., 2018) whereas Chelsa underestimated mean temperatures at Colombian weather stations (Bastidas Osejo et al ., 2019). Our results inform choice of gridded datasets for different applications.…”
Section: Discussionmentioning
confidence: 99%
“…Information regarding vegetation comes mostly from Governmental institutes, as well as the detailed land use information that was also obtained from regional, territorial development plans. In the same way, a review of the results of the model and a comparison with results of other studies nearby, in tropical or similar areas was made [25][26][27][28][29][30][31], to verify the veracity of the results and ensure that they are within a correct range of magnitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, WC corresponds to a set of average monthly interpolated climate data from meteorological stations on a multi-resolution grid [15]. These datasets have been validated and used in studies for purposes of flow estimation, evapotranspiration, the estimation of precipitation and its spatio-temporal variability, and for modeling the distribution of pathogen populations in plants as a function of climate [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%